242 Maintaining Surgical Training During the Covid-19 Pandemic; A Novel Use of Surgical Simulators. (4th May 2021) - Aung, M; Obakponovwe, O; Raymond, A; Apostolidis, K; Bahadori, S; Wainwright, T; Middleton, R
Abstract: Introduction: During Covid-19 pandemic, operation theatres limit the number of staff during each session, which causes a decrease in training opportunity. To counteract this lapse, the Orthopaedic Research Institute (ORI) designs an innovative training session. During the nationwide lockdown, the closure of the Institute allowed for the transfer of the VirtaMed ArthrosTM (VA), to our NHS facility. VA is a surgical simulator which enables the participant to practise knee arthroscopy. Method: Participants with little arthroscopic experience were included in the study. Three fellowship-trained surgeons conducted daily teaching sessions. Participants were taught necessary arthroscopic skills before undertaking training modules on diagnostic arthroscopy. 90% of the participants attended the session at least three times. At the end of every module, VA generates a score based on parameters which include procedure duration, visualisation of key structures and iatrogenic chondral damage. Structure questionnaires were also used to analyse feedback. Results: The overall confidence and module scores progress with each subsequent session. A keystone of success is the location and ease of access to the simulator. Conclusions: Surgical simulators are a useful tool for surgical education and training. We should encourage their use in the future, especially in the UK surgical training programme.